THE EFFECT OF SALINITY ON THE GROWTH AND DEVELOPMENT OF SOYBEAN VARIETIES - Norboyeva Umida Toshtemirovna; Kamalova Gulnoza Raufovna (Modern American Journals, 2025)
Salinity is among the most critical abiotic stress factors that adversely affect the physiological and morphological development of crops, particularly in arid and semi-arid regions. This study investigates the impact of different soil salinity levels on the growth and development of several soybean (Glycine max L.) varieties, which are strategically important leguminous crops in the global food and protein supply chain. The objective of the research was to assess how salinity influences specific agronomic traits, such as plant height and leaf surface area expansion, which are key indicators of plant health and productivity. Controlled experiments were conducted under varying salinity regimes, and a comparative analysis of the growth responses among the soybean varieties was carried out. The findings demonstrate that soil salinity significantly affects the growth rate and leaf morphology of soybean plants. Notably, genotypic variability was observed among the tested varieties in their tolerance to salinity stress. Some varieties showed relatively stable growth under moderate salinity levels, indicating potential for cultivation in marginal and salt-affected soils. The correlation between salinity levels and biomass development revealed that both physiological adaptability and genetic resistance play crucial roles in plant performance. This study provides valuable insights for breeding programs aimed at improving salt tolerance in soybean and highlights the necessity of integrating molecular, physiological, and agrotechnical approaches to ensure sustainable production under stress-prone conditions. The results also contribute to the broader field of plant stress biology and legume crop resilience under changing environmental conditions.
Keywords: Abiotic stress, salinity stress, soybean varieties, physiological response, morphological traits, leaf surface area, leguminous crops, breeding, sustainable agriculture, soil management.